Changes in monocyte subsets in volunteers who received an oral wild-type Salmonella Typhi challenge and reached typhoid diagnosis criteria - Toapanta, Franklin R.; Hu, Jingping; Shirey, Kari Ann; Bernal, Paula J.; Levine, Myron M.; Darton, Thomas C.; Waddington, Claire S.; Pollard, Andrew J.; Sztein, Marcelo B. (Frontiers in Immunology, 2024)
An oral Controlled Human Infection Model (CHIM) with wild-type S. Typhi was re-established allowing us to explore the development of immunity. In this model, ~55% of volunteers who received the challenge reached typhoid diagnosis criteria (TD), while ~45% did not (NoTD). Intestinal macrophages are one of the first lines of defense against enteric pathogens. Most organs have self-renewing macrophages derived from tissue-resident progenitor cells seeded during the embryonic stage; however, the gut lacks these progenitors, and all intestinal macrophages are derived from circulating monocytes. After infecting gut-associated lymphoid tissues underlying microfold (M) cells, S. Typhi causes a primary bacteremia seeding organs of the reticuloendothelial system. Following days of incubation, a second bacteremia and clinical disease ensue. S. Typhi likely interacts with circulating monocytes or their progenitors in the bone marrow. We assessed changes in circulating monocytes after CHIM. The timepoints studied included 0 hours (pre-challenge) and days 1, 2, 4, 7, 9, 14, 21 and 28 after challenge. TD participants provided extra samples at the time of typhoid diagnosis, and 48-96 hours later (referred as ToD). We report changes in Classical Monocytes -CM-, Intermediate Monocytes -IM- and Non-classical Monocytes -NCM-. Changes in monocyte activation markers were identified only in TD participants and during ToD. CM and IM upregulated molecules related to interaction with bacterial antigens (TLR4, TLR5, CD36 and CD206). Of importance, CM and IM showed enhanced binding of S. Typhi. Upregulation of inflammatory molecules like TNF-α were detected, but mechanisms involved in limiting inflammation were also activated (CD163 and CD354 downregulation). CM upregulated molecules to interact/modulate cells of the adaptive immunity, including T cells (HLA-DR, CD274 and CD86) and B cells (CD257). Both CM and IM showed potential to migrate to the gut as integrin α4β7 was upregulated. Unsupervised analysis revealed 7 dynamic cell clusters. Five of these belonged to CM showing that this is the main population activated during ToD. Overall, we provide new insights into the changes that diverse circulating monocyte subsets undergo after typhoid diagnosis, which might be important to control this disease since these cells will ultimately become intestinal macrophages once they reach the gut.